On the mechanical characteristics of the surface layers of the elements of friction units "neck-cover-liner" - Кубич, В.И.; Ивщенко, Л.И. (Problems of Tribology, 2014)
The results of measurements of values of mechanical properties -modulus of elasticity and microhardness of surface layers of the elements of friction units, "neck-cover - liner " for the necks of materials (steel 45 iron VCH50), anti-friction alloy liner AO20-1, the coating on the neck (bronze BrOF4-0,25, the components of gallium indium-medium), tested in conditions of destruction and renewal of the oil layer composition in the contact zone. Obtained pattern of changes in the depths of the contact layer with the appearance of the properties of gallium-indium component of the medium. For information about the nature of the changes discussed earlier mechanical characteristics of the authors were not known to have been obtained and submitted them for the first time.